Scheduling of pipeline construction projects using simulation - Zahran, Hany Mohsen (AUC Knowledge Fountain, 2016)
Repetitive Projects represent a large percentage of construction projects. They usually have an immense importance for a nation’s economy and future. Highways, tunnels, infrastructure networks, high-rise buildings, housing projects, pipeline networks, airport runways, railways, bridges, sewer mains and mass transit systems are all considered projects of repetitive nature. Research that started to serve industrial purposes for the military efforts in World War II has been revised and improved to be employed for repetitive construction projects. Obtaining an optimum schedule that would be achievable, feasible, and comprehensive by all involved parties besides maintaining minimum overall cost and duration has been an important objective. Another main objective was to maintain an optimal formation of various types of crews and equipment that would avoid idle periods as well as work stoppages. Various examples of mathematical models presented in the literature were presented as an example to show their limitations. This research presents a simulation-based scheduling model for pipeline construction projects. The model was developed with a simulation software called “AnyLogic”; this software supports discrete events, agent based and system dynamics simulation, presents an easy graphical user interface and utilizes Java coding. The model consists of various types of pre-programmed objects that were used and connected together to model the different stages of the project and resources involved within them. The model also contains a simulation experiment that would be used to provide the visual presentation of the construction process including the layout of the project and all kinds of utilized resources moving within it. The final part of the model is the optimization module. This module has the definition of the optimization objective, the optimization parameters and constraints. This module would run the simulation experiment a numerous trials while changing the parameters to get the optimal solution which is the optimal schedule for the project. This simulation model would aid planners in scheduling, tracking and controlling the construction operations over the lifetime of the project. It would present an important tool for top management to visualize the impact of their decisions.